Antibacterial Activity of Leaf Extracts from Azadirachta indica A. juss and Solanum trilobatum Linn - SANTHI*, P.R.; POONGOTHAI†, G. (Asian Journal of Chemistry, 2024)
In this study, the antimicrobial activity of Azadirachta indica A. juss and Solanum trilobatum Linn plants leaves were taken for the study. The green leaves of the Azadirachta indica A. juss and Solanum trilobatum Linn plants, was extracted by aqueous method in aspetical manner. Whatman filter paper No.1, discs were used impregnation in the aqueous solution Azadirachta indica A. juss and Solanum trilobatum Linn extract and dried at 37 ºC and sterilized in air oven at 80 ºC for 2 h. The medicinal efficacy was examined against Escherichia coli and Klebsiella pneumoniae by observing the sensitive zone to the herbal extract discs.